Lateinamerikapolitik: un modelo de política exterior alemana hacia América Latina - Villamar, Zirahuén (El Colegio de México A.C., 2025)
From the German perspective, relations with Latin America and the Caribbean have a systemic dimension: a wide range of public and private actors participate in the formulation, decision-making, and implementation of foreign policy toward the region, known as Lateinamerikapolitik. This article analyzes the constituent elements of this framework—its interests and dynamics—through the lens of foreign policy analysis (FPA), with particular attention to organizational and bureaucratic decision-making models. It advances a multidimensional analytical model for examining Lateinamerikapolitik in the 21st century, with the aim of enriching scholarship on German–Latin American relations.